Preparation and properties of microencapsulated lauric acid phase change material incorporated in glass sheet for thermal regulation - Gecain, Ma. Kristina R. (College of Engineering, University of the Philippines Diliman, 2015)
The phase change material (PCM) used in this study was subjected to microencapsulation and then incorporated in a glass sheet and finally tested in an incubator for agricultural application. Lauric acid with enthalpy of 212.47 J/g was encapsulated in a silica shell using sol-gel method. This method was modified by varying parameters such as pH, mixing ratio, drying temperature and drying time. The products were subjected for preliminary characterization using FT-TR and DSC. It was found that the sample with 1:1:2 ratio of TEOs:EtOH:H2O, with pH-1.92 and drying condition of 100C for 7hr has minimal change in the core's latent heat of fusion. This sample was repeated and coated on a glass sheet. The final characterization includes additional analysis such as SEM and Thermal Conductivity test. The glass with silica microencapsulated lauric acid exhibited potential application for energy conservation in incubators.